MOBILE LEARNING AGRIBISNIS UNTUK MENDUKUNG PEROLEHAN LIFESKILL DAN HOTS SISWA SMK - Budi Prasetyanto H.S (Universitas Batanghari Jambi, 2017)
The rapid growth of mobile devices make opportunity and challange to a teacher as educator to use it as media and learning resources. Mobile devicehave connectivity to internet instanly supporting learning principle anywhere and anytime. Based on the researches, mobile learning to support instruction process, to enhance lifeskill, to enhance outcome and learning practice, collaboracy andstudent cooperatif, meta-cognition, or on the other words to support higher order thinking skills-HOTS.Keywords: mobile learning, HOTS, agribussiness,vocational